Others in Deeply Divided Societies: A Research Agenda. Issue 3 (3rd July 2018) - Agarin, Timofey; McCulloch, Allison; Murtagh, Cera
Abstract : This article identifies a central problem in the theory and practice of democracy in divided societies: the systematic exclusion of Others. Defining the exclusion-amid-inclusion (EAI) dilemma of consociational power-sharing, whereby in including the main groups to the conflict it works to exclude those beyond these groups, the article offers the first systematic conceptualization of this issue. The article outlines the type of individuals and groups affected by the EAI dilemma, the varying strategies they adopt to navigate power-sharing frameworks and the potential routes out of this normative and empirical puzzle. Finally, it lays out a challenge for scholars to build on this conceptualization and address the EAI dilemma in future research.